SAT0179 Back pain and disability before, and after, clinically-diagnosed vertebral fractures. (1st June 2001) - Nevitt, M; Palermo, L; Thompson, D; Bauer, D; Stone, K; Ensrud, K; Fink, H; Black, D
Abstract : Background: Painful vertebral fractures that come to medical attention (CVFx) comprise less than a third of all new vertebral deformities (VDef), yet account for a large proportion of the pain and disability due to vertebral osteoporosis. Little is known about the natural history of back pain and related disability before and after a CVFx. Objectives: We compared prefracture levels of back pain and back disability in women who subsequently experienced a CVFx to levels of back pain and disability in women who did not have a CVFx, and examined the duration of increased back pain and disability for 12 months following a CVFx. Methods: We studied 6, 459 women in the Fracture Intervention Trial, aged 55–80 with femoral neck BMD T-score < -1.6. 33% had a baseline VDef. CVFx were self-reported community-diagnosed spine fractures confirmed by central comparison of the diagnostic spine films with the study baseline spine films. Back pain and back-related disability (score 0–20) in the past 4 weeks and number of days back disability (bedrest + limited activity) in the previous 12 months were assessed at baseline (prefracture) using validated instruments. Number of days of severe back pain and disability due to back pain were evaluated for successive 3 month intervals before, and after, a CVFx. Baseline and new VDef during 3 to 4.5 yrs of follow-up were assessed with morphometry. Results: Women who had a single new CVFx > = 6 months after baseline had greater baseline disability than women who had neither a CVFx nor a VDef during FU, adjusting for age, number of baseline VDef, spine BMD, prior Dx of spine fracture, Geriatric Depression Score and treatment assignment. Women with only a new VDef but no CVFx had intermediate levels of prefracture back pain and disability. Women suffering a CVFx reported a mean of 6 days of severe back pain and 6 days of back disability for the 3 month period before the fracture, and 18 and 32 days (both P < .05 by Wilcoxen test), respectively, for the 3 month period after the fracture. By 5–7 months postfacture mean days of severe back pain were no longer elevated (10; P = . 44), but mean days of disability were still increased (24; P < . 05) at 9–11 months post fracture. Conclusion: Older women who have chronic back pain are more likely to suffer a CVFx. In those who have a CVFx, average back disability remains above prefracture levels for at least a year after the fracture. Prevention of fractures may be especially beneficial in older women with chronic back pain.